PERILAKU KEUANGAN KOMUNITAS SENIMAN MOJOPOLO JAWA TENGAH DITINJAU DARI LITERASI KEUANGAN DAN GAYA HIDUP - Ari Susanti; Ester Dwi Supriyanto (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine financial literacy and lifestyle influences on financial behavior in members of the Mojopolo Artist community. This study uses a quantitative approach. The sample of this study was active members of the Mojopolo Artist community, with a total of 98 members. The analysis used multiple linear regression analysis using SPSS 25. Based on the analysis and discussion of financial literacy, lifestyle, on the financial behavior of members of the Mojopolo artist community, financial literacy and lifestyle have a significant effect on financial behavior in members of the Mojopolo artist community.